Dynamics Analysis of Inner Displaced Indexing Cam Mechanism based on Virtual Prototyping Technology - Li Yanqi; Zhao Xili; Guo Junbo; Liu Mingtao; Shi Peifeng (Jixie chuandong)
According to the dynamic characteristics analysis of inner displaced indexing cam mechanism,a dynamic modeling method based on rigid flexible coupling is put forward under the consideration of elastic deformation,inertia load and so on. By using the Solid Works,ADAMS and ANSYS,the rigid flexible coupling dynamics simulation model of Inner displaced indexing cam mechanism is built,the influences of the contact force and the load and rotational speed on dynamic performance of the machine are analyzed. The results of research show that in the same indexing period,the biggest contact force between the cam and single pin appear near the output angle of 20° in certain conditions. With the increase of load,mechanical vibration is increased.And with the increase of rotational speed,the amplitude of the acceleration of the output axis is increased significantly and the contact force between cam and pin is also increased. The different rotational speeds have great influence on the dynamic indexing accuracy of inner displaced indexing cam mechanism.